PRAKTIK TAJDIDUN NIKAH PADA MASYARAKAT PERSPEKTIF HUKUM ISLAM (Studi Kasus di Desa Sidokumpul Kecamatan Bungah Kabupaten Gresik) - Khosiatul Qomariyah; Abdullah Afif (JURNAL ILMIAH NUSANTARA, 2025)
Marriage is the process of uniting a man and a woman through ijab qabul. Behind this process, there is divine wisdom, where strengthening the bonds of marriage, maintaining household harmony is a form of caution towards the validity of marriage. This tradition is known by local terms such as "nganyari nikah" or "remarriage" without a previous divorce. The research method used is qualitative with a sociological approach through interviews, observations and documentation studies. The results of the study show that the practice of Tajdidun nikah in Sidokumpul Village is carried out by fulfilling the pillars and requirements of marriage according to Islamic law, from the factors that cause people to carry out Tajdidun nikah to strengthen their marriage commitment. although there is no explicit legal basis in the Qur'an or hadith. However, scholars have different opinions regarding the permissibility of this practice; some allow it as a form of caution (ihtiyath) while others provide certain limitations so as not to make marriage a game